Systematic Review of Acceptance and Commitment Therapy in Individuals with Neurodevelopmental Disorders, Caregivers, and Staff. Issue 5 (September 2022) - Garcia, Yors; Keller-Collins, Anastasia; Andrews, Meredith; Kurumiya, Yukie; Imlay, Kaleiya; Umphrey, Brandon; Foster, Elizabeth
The purpose of this review was to quantitatively synthesize studies using acceptance and commitment therapy (ACT) with individuals with neurodevelopmental disorders (NNDs), their parents, and staff members that support them. Thirty studies published in peer-reviewed journals between 2006 and 2020 met inclusion criteria. They were reviewed and coded on variables associated with participants' characteristics, settings, dropouts, design type, ACT procedures and measures, social validity, treatment integrity, and main findings. The What Works Clearinghouse (WWC), the revised Cochrane risk-of-bias tool for randomized trials (RoB2) and the Risk of Bias in Nonrandomized Studies of Interventions (ROBINS-I) were applied to evaluate the quality of the studies. Results indicated that 20 studies used group designs and 10 studies used single-case designs. Participants with NNDs consisted predominantly of those with autism spectrum disorder, attention deficit hyperactivity disorder, and learning disabilities. Group studies reported process and outcome measures exclusively; whereas, single-case studies also incorporated behavioral/direct measures. Overall, results showed mixed improvements across studies using indirect and direct measures. Lastly, quality assessment for group studies presented moderate or serious risk of bias and two single-case studies did not meet WWC evidence of effectiveness. Directions for future research and practice are discussed.